Research on Primary Care: a necessity and a challenge to health professionals - Barría P., Mauricio (Investigación y Educación en Enfermería, 2016)
Primary Care (PC) has acquired a fundamental role in the health sector and has been considered a pillar of systems oriented from a more preventive than curative model. Nonetheless, even with the policy emphasis and adoption of family and community models, gaps exist that prevent reaching optimal results from the vision of quality, efficiency, and equity. Within this scenario, research on PC constitutes an essential tool as sustenance of the different actions in this level of care, aimed at increasing the efficacy, effectiveness, and efficiency of programs, actions, and interventions; in addition to promoting the permanent search and innovation of the habitual practice. Thus, research on PC is fundamental to contribute to improving the health of people and the community’s wellbeing.1 Added to the aforementioned, and from the view of a Evidence-Based Practice, it would be expected that professional decisions on PC also be based on scientific evidence and, with it, increase the need for clinical research at this level.2 How to cite this article: Barría RM. Research on Primary Care: a necessity and a challenge to health professionals. Invest. Educ. Enferm. 2016; 34(2):